KNOWLEDGE, ATTITUDE, AND PRACTICES ABOUT BIOMEDICAL WASTE SEGREGATION AND MANAGEMENT AMONG HEALTH WORKERS AT KAJJANSI HEALTH CENTRE IV, WAKISO DISTRICT UGANDA: A CROSS SECTIONAL STUDY. - Akanduhura, Shamim; Otile, Samuel (Student’s Journal of Health Research Africa, 2024)
Background This study aims to assess health workers’ knowledge, attitudes, and practices towards biomedical waste segregation at Kajjansi Health Centre IV. Methodology This research study was carried out at Kajjansi Health Centre IV. The hospital is located in Kajjansi Town, Busiiro South, Wakiso district Uganda. The hospital segregates waste in color-coded waste bins. Data was collected using a self-administered questionnaire. Data was then analyzed manually through tallying and then entered into a computer. The data gathered was then analyzed using SPSS (Statistical Package for Social Sciences) and results were presented using appropriate tables and graphs. Results The majority of the health workers at Kajjansi Health Centre IV were interns being a population of 29 (47%), doctors being 2 (03%), and lab technicians having the least numbers at 4 technicians from the study. It was also found that most of the health workers collected general and biomedical wastes differently that is 42 of the respondents practiced it and 8 did not carry out the practice. 40 of the respondents picked up waste with rubber gloves when on the ground, while 20 only wore gloves at times and 2 never used gloves at all. When it came to cleaning spills of liquid of biomedical wastes with proper procedure, 40 respondents sometimes practiced the procedure and 20 carried out the proper procedure while 2 did not carry out the procedure. Conclusion Education level, health workers in their specialty played and correlated with the knowledge about health waste disposal and segregation, here medical doctors appeared to have the highest knowledge. Recommendations Health management committees should impose tough measures where all health workers attend training and workshops on biomedical waste management and segregation.